Sports Culture and Its Relationship to The National Affiliation of Students College of Education at The University of Zakho - Sulaiman, Rabee' Mohammed Saleh; Mohammed, Safad Mudhafar; Saleh, Mustafa Majid Mohammed (LP. Ma'arif Janggan Magetan, 2024)
Sports culture significantly influences identity formation, particularly among the youth. This significance is underexplored within the context of Iraqi Kurdistan, prompting this study to explore the connection between involvement in sports culture and national affiliation among university students. The study's objectives were to evaluate the levels of sports culture engagement and feelings of national belonging among the students and to investigate the correlation between these two factors. The research involved a sample of 286 students from the Physical Education and Psychology departments at Zakho University. The methodology included collecting data using a sports culture scale and a national affiliation scale, followed by statistical analysis through T-tests to assess levels and Spearman correlation to examine the relationship between sports culture and national affiliation. The results revealed high mean scores in both sports culture and national belonging scales across both departments, with Physical Education students exhibiting slightly higher averages. Importantly, the study found a moderately strong positive correlation between sports culture involvement and levels of national affiliation. The conclusions drawn from the study suggest that participation in and knowledge of sports culture are linked to increased feelings of national pride and connection among Kurdish university students. This underscores the potential of utilizing sports education and programming as tools to strengthen communal identities. The study recommends further research across different Iraqi populations to explore this relationship further.